Productive Performance, Egg Characteristics and Hatching Traits of Three Chicken Genotypes under Free-Range, Semi-Intensive, and Intensive Housing Systems - Ahmad,S (2019)
ABSTRACT The present study aimed at evaluating the effect of housing system on the live performance, egg quality, and hatching traits of three dual-purpose chicken genotypes. In total, 180 birds, comprising 48 pullets and 12 cockerels from each of three genotypes, were evaluated during the production phase (27-46 weeks). For this, 144 pullets and 36 cockerels were randomly picked from 18 treatment block groups were shifted to breeding coops, allotting 4 pullets to one cockerel. A completely randomized complete block design (RCBD) was employed. Three genotypes, purebred Naked Neck (NN) and two crosses Rhode Island Red × Naked Neck (RIR × NN = RNN) and Black Australorp × Naked Neck (BAL × NN = BNN), were compared. Intensive system (p<0.0001) and BNN hens (p<0.0001) were heavier on week 26 and 46. Higher egg production (p<0.0001) was obtained in the intensive system and in BNN hens (p<0.0001). Hens maintained in the intensive systems produced heavier eggs and higher egg mass (p<0.0001), and RNN and BNN hens laid heavier eggs (p<0.0001) while higher egg mass (p<0.0001) was found in BNN hens. Higher egg shape index (initial, p=0.0002), egg surface area (initial, p<0.0001; final, p<0.0001), egg volume (initial, p<0.0001; final, p<0.0001) and Haugh unit score (initial, p=0.0002; final, p=<0.0001) were obtained in RNN and BNN hens. At the end of the experiment (46 weeks), higher yolk index (p=0.0004) was found in RNN and BNN eggs, and thicker eggshells (p<0.0001) in RNN eggs. Higher egg hatchability was obtained in the free-range system (p<0.0001) and in the RNN genotype (p<0.0001). The highest fertility rates were detected in the free-range system (p<0.0001), and in the RNN and BNN genotypes (p<0.0001). The lowest infertile egg rates were observed in the free-range system (p<0.0001) and in RNN and BNN genotypes (p<0.0001). The lowest dead-in-shell rate was calculated for the free-range system (p=0.0456). In conclusion, free-range and semi-intensive system largely influence productive performance, egg quality and hatching traits. Regarding genotypes, RNN and BNN crossbred hens perform better than NN purebreds.